Asuhan Kebidanan Pada Bayi Baru Lahir Normal Di Puskesmas Panjatan I - Novi Rachmawati (EDUPEDIA Publisher, 2023)
Objective: This study aims to be able to provide midwifery care for newborns according to midwifery management.Methods: This study used a descriptive method, which took place at the Panjatan I Health Center. The research time was from December 2018 to August 2020; the research subjects were newborns at term according to the gestation period. Data collection techniques took primary and secondary data, while data analysis was carried out in this study using qualitative research by intervening in midwifery care.Results: Results of By.Ny. F 6 hours old under normal circumstances. Management provides care on how to keep the baby warm, provides counselling about exclusive breastfeeding, care for the umbilical cord and danger signs for newborns. It is hoped that it can increase knowledge about midwifery care for newborns properly and correctly.Conclusion: The results of the evaluation of the management that was given to Mrs F's baby were that the baby's general condition was good, vital signs were within normal limits, breastfeeding was smooth, the baby was drinking milk > 8x a day, the mother was able to breastfeed her baby with the proper technique, and without help, the mother already understands how to care for the baby daily and can already care for her own baby.